Evil corporations: law, culpability, and regulation - Crofts, Penny (Routledge, 2025)
"This book elaborates and interrogates the idea of evil corporations from a diverse range of disciplines. There has long been awareness of systemic harms inflicted by corporations, but this awareness has rarely led to any effective legal means to prevent and/or respond adequately to them. Lawyers and legal theorists appear to be stuck asking the same questions, and giving the same ineffective answers. Part of the problem, this book maintains, is the relative lack of theoretical interrogation into the nature of corporations as responsible, moral agents. To break this stasis, this book draws upon philosophies of wickedness in order to ask whether or not corporations are, or can be, evil. With contributions from a range of different disciplines, including law, cultural theory, theology, and philosophy, it offers a novel account of how and why corporate wrongs are caused, whilst exploring the extent to which the legal system itself facilitates such wrongdoing. The book is targeted at a broad international audience with research interests in corporate crime. This will be of particular interest to those within the legal discipline including corporate law, criminal law, corporate crime and law and humanities scholars"--